Inter-orbital Inter-satellite communication link performance analysis at THz band considering gravity-induced antenna pointing error - Lyu, Junyi (2025)
Inter-satellite communication (ISC) plays a vital role in low Earth orbit (LEO) satellite communication systems, enabling seamless communication among satellites located within the same or different orbital planes. This paper investigates the link performance of LEO satellites at terahertz (THz) band, taking the distance between the LEO satellites and satellite position perturbations into account. The performance metrics for the link, including the average bit error rate (BER), outage probability and ergodic capacity are formulated and employed to assess the performance of inter-orbital ISC at THz band. Simulation results demonstrate that an increase in the variance of the beam misalignment angle reduces the accuracy of the ISC link, resulting in a higher average BER and outage probability. Furthermore, optimal central frequency selection is essential to achieve the highest ergodic capacity for different variances, with the potential for reaching tens or even hundreds of gigabits per second (Gbps)